ANALYSIS ON FLOW CHARACTERISTICS OF COMBINATION AIR VALVE PROTOTYPE USING CFD TECHNIQUE: A 2D-VOF MODEL - Promtong M. (2023)
Due to vacuum and safety issues, combination air valves are necessarily introduced to evacuate the entrapped air before damaging piping system components. This research was aimed to introduce the Computational Fluid Dynamic (CFD) technique to investigate the flows in a combination air valve, especially while releasing the air under various operating conditions. A two-dimensional model was proposed to perform the simulation study to save the computing time. The boundary and conditions were derived from the actual experiment; specifically, the Volume of Fluids (VOF) method was employed to capture the interfacial motion of the air-water flows. The turbulent model, Realizable κ-ε, was adopted to calculate the Reynolds Stress term. As a result, the predicted transient pressures, and the calculated air release times of both the cases installing and not installing the SARC agreed with the experiments; the maximum differences were 8.8% and 16.4%, respectively. According to the simulation works, it was found that the crucial factors to consider to evaluate air valve performance are transient pressure and velocity fields in the air valve and the transient force acting on the ball valve. In future work, a more comprehensive study will be conducted to find the critical criteria for the combination air valve design, especially to enhance the air removal performance.